Women's empowerment and household decision-making: Charting the knowledge base and emerging research frontiers. - Mohd Ishak@Zainudin, Fadhilah; Abdul Rahman, Firdaus; Mat Nawi, Hafizah; Abdul Rahman, Khadijah; Sapiai, Nur Shaliza (International Journal of Accounting, Finance and Business, 2026)
Women's empowerment in household decision making has emerged as a significant topical issue and debate among scholars. Under the Sustainable Development Goals (SDGs) 2015, one of the goals is to achieve gender equality and women empowerment. The importance of this goals which has become a national agenda has necessitated this to study to identify the relevant factors that are associated with women empowerment as well as to narrow the gender inequality gap. This study presents a bibliometric analysis of published research on women's empowerment in household decision making, drawing on publications retrieved from the Scopus databases covering the period from 1986 to 2026. The database was filtered to include peer reviewed journals and 606 documents were extracted. The published papers have been analysed using bibliometric parameters and systematically examines the volume and growth of scholarly output, identifies the most leading authors, journals, and countries. While for the citation analysis, the study employs Harzing’s Publish or Perish Program to integrate the data. Based on the data, it shows that studies examining women empowerment and household decision making are becoming prominent with the rising trend of annual publications as well as citations. It is found that most of the research of women empowerment was carried out in United States, India, Bangladesh and United Kingdom. Hence, this study contributes to the literature by providing a structured overview of the current state of knowledge, identifying research gaps, and offering directions for future research in this increasingly policy relevant field,